Securing Democracy by strengthening the rule of law - Spasov, Aleksandar (Foundation for European Progressive Studies and European Parliament, 2022)
Since 2020 the European Union has defined the rule of law as one of the fundamentals in its new methodology for the EU accession process, thus underlining its importance as a core European value. Despite their reform efforts, all countries of the Western Balkans are still struggling with organised crime and corruption, clientelism in their institutions, a weak judiciary, and low levels of trust from citizens in their government system. This poor condition of the rule of law undermines the public's trust in the effectiveness of democracy. In the long run, this could have disastrous effects on the democratic consolidation in the Western Balkans.